2013
DOI: 10.1111/cpr.12027
|View full text |Cite
|
Sign up to set email alerts
|

Character comparison of abdomen‐derived and eyelid‐derived mesenchymal stem cells

Abstract: Although isolated from similar adipose tissues, both types of cells displayed many contrasting characteristics. Understanding defining phenotypes of such cells is useful for making suitable choices in differing clinical indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
(32 reference statements)
2
12
0
Order By: Relevance
“…MSCs were first characterized from bone marrow, adipose and embryonic tissues and are well-documented to travel to tumor sites [ 8 - 10 ]. MSCs have now been reported in a variety of other tissues including ovary, brain, spleen, liver, kidney, lung, muscle, thymus, pancreas, eyelid, and the peri-vasculature [ 11 - 13 ], suggesting MSCs may be present in many tissues throughout tumor initiation and growth.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs were first characterized from bone marrow, adipose and embryonic tissues and are well-documented to travel to tumor sites [ 8 - 10 ]. MSCs have now been reported in a variety of other tissues including ovary, brain, spleen, liver, kidney, lung, muscle, thymus, pancreas, eyelid, and the peri-vasculature [ 11 - 13 ], suggesting MSCs may be present in many tissues throughout tumor initiation and growth.…”
Section: Introductionmentioning
confidence: 99%
“…35 ). Evenmore, it has been shown that adipose derived MSCs possess different abilities according to the tissue of origin 38,39 . Comparison of MSCs from abdominal fat, mesodermal origin, eyelid adipose tissue MSCs, and ectodermal origin, showed different phenotypes of cells together with variety in CD90 expression, suggesting higher abdominal fat MSCs response to angiogeneic factors 38 .…”
Section: Mscs Source Variabilitymentioning
confidence: 99%
“…Evenmore, it has been shown that adipose derived MSCs possess different abilities according to the tissue of origin 38,39 . Comparison of MSCs from abdominal fat, mesodermal origin, eyelid adipose tissue MSCs, and ectodermal origin, showed different phenotypes of cells together with variety in CD90 expression, suggesting higher abdominal fat MSCs response to angiogeneic factors 38 . Comparison of cardiac adipose tissue derived MSCs and abdominal fat MSCs, both of mesodermal origin, showed that cells were phenotypically identical, but cardiac MSCs constituted intristic properties toward myogenesis and vasculogenesis in significantly higher percentage and therefore have much better regenerative potential, especially for cardiac therapy 39 .…”
Section: Mscs Source Variabilitymentioning
confidence: 99%
“…Human eyelid adipose-derived stem cells (HEASCs) are novel MSCs and originated from the neural crest source. In addition, HEASCs are also similar to BMSCs in the growth potential and surface marker expression [ 7 , 9 ]. In addition, HEASCs lacked immunogenicity and were safe and well-tolerated after intravenous injections and topical administration in previous studies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%